Pengaruh Insentif dan Motivasi terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Selatan - Satyawan, Robby; Marnisah, Luis; Wadud, Muhammad (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
This study aims to investigate the effect of incentives and motivation on employee performance at the DPRD Secretariat. Sampling deployed non-probability techniques on the total population of DPRD Secretariat employees. Data of 75 respondents were collected through questionnaires and interviews. This study implemented multiple linear regression methods to analyze data. The results evince that partially, each incentive and motivation has a significant effect on employee performance. Likewise, simultaneously, incentives and motivation have a significant effect on employee performance. This research can benefit the DPRD Secretariat. To improve employees performance, the leaders should consider incentives and motivation factors for employees.